KEBIJAKAN PENGEMBANGAN USAHA BUDIDAYA PERIKANAN PADA LAHAN BEKAS GALIAN TAMBANG PASIR DI KABUPATEN KARAWANG - Tajerin, Tajerin (Jurnal Organisasi dan Manajemen, 2007)
Water potential resources in area of receptacle sand land any wide enough and separated in all over Indonesia, as in District Karawang, West Java, but its utilization estimated still lower. The effort to utilizing that receptacle sand land which can be seen as widely to increase the community social welfare is through one of farming fisheries aquaculture. The objective of this research is to determine appropriate policy for development farming fisheries aquaculture at receptacle sand land in Karawang District, West Java. This research was conducted during January to December 2005, and using Analytic Hierarchy Process (AHP). The result of this study showed that any three policies which is suitable creation, there are policy for increasing and expensing market of fisheries product, policy for institutional capacity development and policy for fisheries infrastructure.